PENGARUH KARAKTERISTIK INDIVIDU DAN KOMPETENSI TERHADAP KINERJA USAHA MELALUI KEWIRAUSAHAAN PADA UMKM DI DESA NGUJUNG TOYOMARTO KEC. SINGOSARI KAB. MALANG - Ardelina Putri (Faculty of Islamic Economics and Business, 2020)
This research is a quantitative study using a Likert scale. The sample used was a total population of 36 sandal craftsmen. The statistical analysis used is path analysis, using SPSS 17 calculations. The objectives of this study are: i) To examine the effect of individual characteristics on business performance; ii) Test the effect of individual characteristics on entrepreneurship; iii) Test the effect of competence on business performance; iv) Test the effect of competence on entrepreneurship; v) Test the effect of individual characteristics on business performance through entrepreneurship; vi) Test the effect of competence on business performance through entrepreneurship; vii) Test the effect of entrepreneurship on business performance.The results showed that: (i) Individual characteristics did not significantly influence business performance; (ii) Individual characteristics do not significantly influence entrepreneurship; (iii) Competence has a significant effect on business performance; (iv) Competence has a significant effect on entrepreneurship; (v) Competence has a significant effect on business performance through entrepreneurship; (vi) Individual characteristics do not significantly influence business performance through entrepreneurship; (vii) Entrepreneurship influences business performance.